Neutrophil-Lymphocyte Ratio in Branch Retinal Vein Occlusion - Doğan, M; Polat, O; Baysal, Z; Ulu, MS; İnan, S; Yavaş, GF; İnan, ÜÜ (International Journal of Human and Health Sciences (IJHHS), 2021)
Objective: Branch retinal vein occlusion (BRVO) is the most common retinal vascular disease following diabetic retinopathy. Pathogenesis of BRVO is multifactorial and could not be clarified enough yet. As BRVO is a disease that goes with thrombosis and inflammatory processes, inflammatory markers could help to predict the risk of BRVO. The aim of this study was to evaluate the association between neutrophil-lymphocyte ratio (NLR) and the BRVO. Materials and Methods: Forty-three patients with BRVO were included to this retrospective study. Forty age and sex-matched healthy volunteers were recruited as the control group. Demographic characteristics, white blood cell (WBC), neutrophil, lymphocyte, monocyte, platelet counts and NLR were recorded and compared between the patients and the control group. Results and Discussion: The mean WBC, neutrophil and NLR were significantly higher in the BRVO patients compared with control group (7.89±1.8fL vs 6.97±1.4fL, p=0.014, 4.85±1.4fL vs 4.01±0.9fL, p=0.002, 2.40±1.2 vs 1.87±0.5, p=0.026, respectively). There were no difference between two groups in terms of lymphocyte, monocyte and platelet counts (p=894, p=0.22, p=0.589, respevtively). Conclusion: NLR was higher in patients with BRVO and higher NLR may contribute to development of BRVO associated with systemic and/or local inflammation. International Journal of Human and Health Sciences Vol. 05 No. 04 October’21 Page: 499-502